Analysis and Design Data Warehouse For E-Travel Business Optimization - I Nyoman Angga Prabawa; Dewa Agung Krishna Arimbawa P; I Gusti Ngurah Janardana (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2019)
Tourism, accommodation, and transportation service industries are business with high prospects, especially in Bali. Development of digital technology into the e-travel industry has business processes that can be optimized through a data warehouse with a variety of data as the initial start of analyst business data. A problem reality is less and almost no travel company has developed a data warehouse to support business needs. Building a data warehouse is a technology to increase business value through data analysis on a variety of stored data. Using the fourth steps dimensional modeling methodology, the data warehouse is expected to be in accordance with the company's analysis to increase business needs. The design results consist of determining business processes, grain declaration on dimensions, identifying dimensions, and determining facts. The design results using snowflake scheme and become a solution for companies to predict business trends, maintain quality, improve competitiveness, and exist in the long run